2018
DOI: 10.1001/jama.2017.20885
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality in NFL Professional Football Players

Abstract: The many positive health benefits of regular exercise, including longer lifespan, outweigh the risks of being physically active from both an individual and a population standpoint. Although the risks of extreme sports and other activities with inherent risks are tolerated by participants and fans, there has been a resurgence of interest in the health of those who participate in contact sports, notably professional American football, as well as hockey, lacrosse, soccer, rugby, and other sports in which concussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…1 GDM exposure was divided into diagnosis by or after 26 weeks' gestation based on a prior finding that risk of ASD was elevated for exposure to GDM by 26 weeks. 1 T1D was identified using the algorithm developed for electronic health records data 2 and confirmed by prescription of insulin during pregnancy. Potential confounders were birth year, maternal age at delivery, parity, education, selfreported race/ethnicity, median family household income based on residence census tract, history of comorbidity (≥1 diagnosis of heart, lung, kidney, or liver disease; cancer), and child's sex.…”
mentioning
confidence: 99%
“…1 GDM exposure was divided into diagnosis by or after 26 weeks' gestation based on a prior finding that risk of ASD was elevated for exposure to GDM by 26 weeks. 1 T1D was identified using the algorithm developed for electronic health records data 2 and confirmed by prescription of insulin during pregnancy. Potential confounders were birth year, maternal age at delivery, parity, education, selfreported race/ethnicity, median family household income based on residence census tract, history of comorbidity (≥1 diagnosis of heart, lung, kidney, or liver disease; cancer), and child's sex.…”
mentioning
confidence: 99%
“…The sustained positive effects of physical activity and recreational sports with moderate to slightly intensive exertion on health, well-being, mobility, and mortality have been well-examined and empirically proven (Blair et al, 1995 ; Kujala et al, 1998 ; Garber et al, 2011 ; Turi-Lynch et al, 2019 ). In contrast, empirical evidence of long-term health effects caused by extensive elite sports and of the associated life expectancy is less comprehensive and more heterogeneous (Beaglehole and Stewart, 1983 ; DeKosky et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses and systematic reviews by Garatachea et al ( 2014 ), Lemez and Baker ( 2015 ), and Teramoto and Bungum ( 2010 ) consistently showed higher life expectancies or lower mortality rates in elite athletes vs. the comparative population, although Venkataramani et al ( 2018 ) found no differences between 3812 National Football League players in the 1982 to 1992 seasons and the general population (Beaglehole and Stewart, 1983 ; DeKosky et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A robust body of research finds that professional American football players (hereafter, “football players”) live longer than men in the United States in general ( 1 7 ). On the surface, this finding might seem surprising given publicity and research about high rates of cardiovascular ( 8 12 ) and neuropsychological problems (many resulting from traumatic brain injuries) ( 13 18 ) among football players.…”
mentioning
confidence: 99%